2014
DOI: 10.3390/md12115657
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Chemodiversity and Biological Activities of the Secondary Metabolites from the Marine Fungus Neosartorya pseudofischeri

Abstract: The production of fungal metabolites can be remarkably influenced by various cultivation parameters. To explore the biosynthetic potentials of the marine fungus, Neosartorya pseudofischeri, which was isolated from the inner tissue of starfish Acanthaster planci, glycerol-peptone-yeast extract (GlyPY) and glucose-peptone-yeast extract (GluPY) media were used to culture this fungus. When cultured in GlyPY medium, this fungus produced two novel diketopiperazines, neosartins A and B (1 and 2), together with six bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 37 publications
3
49
0
Order By: Relevance
“…Indeed, gliotoxin significantly inhibits growth of a range of fungi, 12,46 and previously work has also indicated its potent anti-bacterial activity. 47 It is clear that interference with intracellular DTG levels, via gliotoxin exposure to A. fumigatus DgliT impacts on the fungal proteome, which in turn can be modulated by Zn 2+ presence.…”
Section: +mentioning
confidence: 99%
“…Indeed, gliotoxin significantly inhibits growth of a range of fungi, 12,46 and previously work has also indicated its potent anti-bacterial activity. 47 It is clear that interference with intracellular DTG levels, via gliotoxin exposure to A. fumigatus DgliT impacts on the fungal proteome, which in turn can be modulated by Zn 2+ presence.…”
Section: +mentioning
confidence: 99%
“…There is evidence to suggest that gliotoxin is a promising anticancer reagent that induces cytotoxic effects on cancer cells (21)(22)(23). Previously, we observed that reduced-exerted the most potent anticancer effects compared to other gliotoxin analogues (14). In this study, we examined the potency of reduced-gliotoxin against CRC cells and the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…Reagents details and use. Reduced-gliotoxin was isolated from the secondary metabolites of the marine fungus, Neosartorya pseudofischeri, following the procedure described previously (14). The purity of reduced-gliotoxin was >98% as determined by high-performance liquid chromatography (HPLC).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations